Pengaruh Gender Terhadap Pengambilan Keputusan di Lingkungan Kerja - Dani Finata Pratama; Harmon Chaniago (Jurnal Riset Bisnis dan Investasi, 2017)
In a work environment, employees from the staff level to top management once confront a problem that requires decision-making. Gender is a very influential factor in decision making. Gender defined here is not “gender”. It is the attitudes or attributes of a man or woman that can change over time and working conditions. This study aims to determine the effect of employee gender differences, knowing the ability of employee decision making and to know how much influence gender to decision making in the working environment of PT Jasa Marga (Persero) Tbk. Purbaleunyi Branch. The research method used is descriptive analysis, classical assumption test, correlation analysis, simple regression analysis, and hypothesis test. The sample in this study were 114 respondents consisting of employees of data processing, staff, up to senior officer. Data collection was done by distributing questionnaires and interviewing employees. Based on the results of data, gender and decision making are in good category. The conclusion of this research is gender influence toward decision making 57,3%.